2012
DOI: 10.1002/ptr.4829
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Decreases Connective Tissue Growth Factor to Improve Liver Fibrosis in Rats Treated with Carbon Tetrachloride

Abstract: Silymarin is an herbal product showing potential as protection against hepatic disorders. In an attempt to develop the agent for the treatment of hepatic fibrosis, we screened the effects of silymarin on a rat model of hepatic fibrosis induced by carbon tetrachloride (CCl₄). Intraperitoneal administration of CCl₄ to rats for 8 weeks not only increased the plasma levels of glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) but also induced a marked increase in the formation of hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…34 Smad3 signaling has been identified as the responsible pathway inducing CTGF expression in hepatocytes of CCl 4 -treated mice, 35 and knockdown of CTGF by injection of small interfering RNA into the portal veins of rat livers prevents CCl 4 -induced fibrosis by inhibiting TGF-b induction and HSC activation. 36 It has been reported that in rats treated with CCl 4 silymarin decreases CTGF to improve liver fibrosis 37 and curcumin significantly attenuates the severity of liver damage through inhibition of CTGF expression. 30 Our findings confirmed that chronic CCl 4 administration markedly enhanced the intrahepatic expression of CTGF mRNA and protein, and that melatonin significantly reduced these CCl 4 -induced increases.…”
Section: Discussionmentioning
confidence: 99%
“…34 Smad3 signaling has been identified as the responsible pathway inducing CTGF expression in hepatocytes of CCl 4 -treated mice, 35 and knockdown of CTGF by injection of small interfering RNA into the portal veins of rat livers prevents CCl 4 -induced fibrosis by inhibiting TGF-b induction and HSC activation. 36 It has been reported that in rats treated with CCl 4 silymarin decreases CTGF to improve liver fibrosis 37 and curcumin significantly attenuates the severity of liver damage through inhibition of CTGF expression. 30 Our findings confirmed that chronic CCl 4 administration markedly enhanced the intrahepatic expression of CTGF mRNA and protein, and that melatonin significantly reduced these CCl 4 -induced increases.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of CCl 4 toxicity on P450-mediated metabolism means that, similar to APAP, interventions which inhibit metabolism will likely protect against injury. Unfortunately, many studies showing protection against CCl 4 hepatotoxicity by herbal therapeutics have relied on either pretreatment or cotreatment (Kang et al, 2008; Dhanasekaran et al, 2009; Risal et al, 2012; Tzeng et al, 2012). Thus, any conclusions regarding an anti-inflammatory, antioxidant, or anti-fibrotic effect in these and similar studies are questionable at best.…”
Section: Non-acetaminophen Models Of Hepatotoxicitymentioning
confidence: 99%
“…The whole extract, known as silymarin, as well as silybin, has been found to protect the liver from both acute and chronic toxicity and injury (1720). Previous studies have demonstrated that silybin inhibits various inflammatory responses by suppressing the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%